Theology and science in the thought of Francis Bacon - Matthews, Steven, 1969- (Ashgate Pub., 2008)
Although many books have been published on Francis Bacon there is still no scholarly consensus on his religious beliefs and how they may have affected his work. This monograph contributes possible answers to the questions of what Bacon believed and how it may have affected the development of his program for scientific reform, the 'Great Instauration'. The work also offers a new approach to the question of the interaction of religion and science in early modern England by considering the effect of patristic theology on the development of new ways of considering the relationship of God and natur.